Mass transport limitation in inlet periphery of fuel cells: Studied on a planar Solid Oxide Fuel Cell. (6th September 2018) - Aydın, Özgür; Ochiai, Tatsuhiro; Nakajima, Hironori; Kitahara, Tatsumi; Ito, Kohei; Ogura, Yusuke; Shimano, Jun
Abstract: It was recently clarified on a microtubular Solid Oxide Fuel Cell (SOFC) that the range of mass transport limitation might commence from the inlet periphery (inlet opening and inlet pipe), i.e., the concentration gradient of reactants may extend inward the inlet periphery. For demonstrating that this phenomenon occurs regardless of the form and type of the fuel cell operating at high reactant utilization rate, herein we investigate the mass transport in the anode side of a one-cell stack of a planar SOFC. The investigation leans upon experimental and numerical data analyzed from both conventional (non spatial) and spatial perspectives. The experimental data were spatially obtained in the lateral direction by applying the segmentation method. Regarding analyses let us to confirm that mass transport limitation occurs in the inlet periphery of the planar stack. Besides, the critical ratio of the consumed/supplied mass fluxes of hydrogen is valid for assessing whether the concentration gradient of hydrogen extends inward the inlet periphery. Furthermore, the virtual inlet opening is useful for accurately calculating the mass transport within the active field of the stack via hypothetically preventing the mass transport limitation in the inlet periphery. These findings are expected to help researchers and engineers for accurately designing and characterizing fuel cell systems at varying scales from cells to stacks. Highlights: Extension of concentration gradient of reactants inward the inlet periphery. Inlet opening is the crucial part of inlet periphery determining inlet mass flux. Ratio of consumed/supplied mass fluxes whether to consider inlet periphery. Critical ratio of consumed/supplied mass fluxes is 4 × 10 -3 at 1073K for H2 -N2 -H2 O. Virtual inlet opening helps for accurately computing mass transport.